Sign language instrument for assessing the knowledge of deaf people about Cardiopulmonary Resuscitation - Nelson Miguel Galindo-Neto; Magno Batista Lima; Lívia Moreira Barros; Silvana Cavalcanti dos Santos; Joselany Áfio Caetano (Revista Latino-Americana de Enfermagem)
Objective: to build and validate the content on Cardiopulmonary Resuscitation (CPR) of a sign language instrument for assessing the knowledge of the deaf. Method: methodological study in which the content validity process was used by 22 specialists in cardiac arrest and 16 deaf people. In the validation of internal consistency, 113 deaf people participated. For the assessment of the deaf, the Assistive Technology Assessment Questionnaire was used and, in the content validity, an instrument with a Likert scale was used, which included the content, clarity, objectivity, organization and language. Items with a minimum agreement of 80% were considered valid, according to the Content Validity Index (CVI) and binomial test. The internal consistency was verified by Cronbach’s alpha. Results: The instrument contains 11 questions about the identification of cardiorespiratory arrest, activation by aid and high quality chest compression. It had a minimum content validity of 81% by the specialists, 90% by the deaf participants and internal consistency by the Cronbach alpha of 0.86, being considered high. Conclusion: the instrument can be used in research to survey the previous knowledge of deaf people about CPR, as well as in pre and/or post-testing studies that test educational interventions with this public.